SC35-mediated bZIP49 splicing regulates K⁺ channel AKT1 for salt stress adaptation in poplar - Xiao Liu; Yu Bao; Man-Yu Zhang; Han Zhang; Meng-Xue Niu; Shu-Jing Liu; Mei-Ying Liu; Meng-Bo Huang; Chao Liu; Weilun Yin; Hou-Ling Wang; Xinli Xia (Nature Communications)
Abstract Soil salinization threatens plant distribution, crop yields, and ecosystem stability. In response, plants activate potassium (K+) signaling to maintain Na⁺/K⁺ balance, though the mechanisms regulating K⁺ uptake under salt stress remain poorly understood. This study identified two splice variants of the bZIP49 transcription factor in Populus tomentosa: unspliced “bZIP49L” and spliced “bZIP49S”. bZIP49S, the active form under salt stress, reduces salt tolerance when overexpressed, while bzip49cr knockout enhances it. The serine/arginine-rich splicing factor SC35 was identified as a regulator of bZIP49 mRNA splicing through a self-developed experimental method, and its overexpression enhances salt sensitivity. bZIP49S inhibits the K+ transporter AKT1 by binding its promoter, and AKT1 loss in bzip49cr mutant limits K+ influx and reduces salt tolerance. Under salt stress, the E2 ubiquitin-conjugating enzyme UBC32 promotes SC35 degradation via ubiquitination, lowering bZIP49S levels and alleviating the inhibition of AKT1. This facilitates K⁺ uptake, restores Na⁺/K⁺ balance, and improves salt tolerance. Our study highlights the critical role of bZIP49 splicing and the “UBC32-SC35-bZIP49-AKT1” module in modulating Na⁺/K⁺ balance under salt stress in poplar.